Comparison of surgery results in two risk-adjusted populations through the POSSUM system - Machado, Fernando; Santiago, Pablo; Barberousse, Carlos; Barrios, Enrique; Carriquiry, Luis A (Cirugía del Uruguay, 2002)
Proper evaluation of surgical outcomes is a difficult task and objectives systems of measurements are needed. POSSUM and p-POSSUM are one of such systems recently developed at the United Kingdom, which includes severa! easily and commonly measured clinical·, laboratory and opetative items.